Utilization of In-Hospital Care among Foreign-Born Compared to Native Swedes 1987–1999 - Björn Albin; Katarina Hjelm; Jan Ekberg; Sölve Elmståhl (Nursing Research and Practice)
In previous longitudinal studies of mortality and morbidity among foreign-born and native-born Swedes, increased mortality and dissimilarities in mortality pattern were found. The aim of this study is to describe, compare, and analyse the utilization of in-hospital care among deceased foreign- and Swedish-born persons during the years 1987–1999 with focus on four diagnostic categories. The study population consisted of 361,974 foreign-born persons aged 16 years and upward who were registered as living in Sweden in 1970, together with 361,974 matched Swedish controls for each person. Data from Statistics Sweden (SCB) and the National Board of Health and Welfare Centre for Epidemiology, covering the period 1970–1999, was used. Persons were selected if they were admitted to hospital during 1987–1999 and the cause of death was in one of four ICD groups. The results indicate a tendency towards less health care utilization among migrants, especially men, as regards Symptoms, signs, and ill-defined conditions and Injury and poisoning. Further studies are needed to explore the possible explanations and the pattern of other diseases to see whether migrants, and especially migrant men, are a risk group with less utilization of health care.